PHYSIOLOGICAL ANALYSIS OF CUO BULK AND NANOPARTICLES TO CASTOR (RICINUS COMMUNIS L.) - Mahmoodzadeh, Homa; Eshaghi, Ali; Gholami, Tayebeh (Plant Breeding and Seed Science, 2016)
The rapidly increasing multifarious use of metallic nanoparticles in technology has necessitated evaluation of their impact on environmental, biotic and human health. The present study investigated the effects of different concentrations of bulk and nanosized CuO on seed germination and seedling growth of Ricinus communis in a randomized completely design with four replications. The experimental treatments included four concentrations of bulk CuO (10, 50, 100 and 500 ppm), four concentrations of nanosized CuO (10, 50, 100 and 500 ppm), and the control without CuO. The results indicate that only the weighted germination index and seedling dry biomass of Ricinus communis were significantly affected by the treatments. Other germination characteristics, plumule and radicle length, and seedling fresh weight were not significantly affected by bulk and nanosized CuO concentrations. It can be concluded that bulk and nanosized CuO in this cocentrations not toxic for germination and growth of Ricinus communis.